2003
DOI: 10.1111/j.1460-9568.2003.03001.x
|View full text |Cite
|
Sign up to set email alerts
|

Single olfactory sensory neurons simultaneously integrate the components of an odour mixture

Abstract: Most odours are complex mixtures. However, the capacities of olfactory sensory neurons (OSNs) to process complex odour stimuli have never been explored in air-breathing vertebrates. To face this issue, the present study compares the electrical responses of single OSNs to two odour molecules, delivered singly and mixed together, in rats in vivo. This work is the first aimed at demonstrating that single OSNs simultaneously integrate several chemical signals and which, furthermore, attempts to describe such proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
142
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(156 citation statements)
references
References 45 publications
14
142
0
Order By: Relevance
“…psychophysically at high detectability has a further neurophysiological correlate, measured as spike frequency of single olfactory neurons [23]. The responses of receptor cells to binary mixtures shifted towards decreasing additivity as the concentration of the mixed chemicals increased.…”
Section: Discussionmentioning
confidence: 99%
“…psychophysically at high detectability has a further neurophysiological correlate, measured as spike frequency of single olfactory neurons [23]. The responses of receptor cells to binary mixtures shifted towards decreasing additivity as the concentration of the mixed chemicals increased.…”
Section: Discussionmentioning
confidence: 99%
“…According to the definition of interactions described by Duchamp-Viret et al (Duchamp-Viret et al, 2003), A1 and A2 neurons showed a 'suppression' type of mixture interaction. Purely excitatory or purely inhibitory responses of B and C neurons to the pheromone were not affected when heptanal was added, thus these neurons exhibited a 'hypoadditivity' type of interaction.…”
Section: Mgc Neurons Are Sensitive To a Behaviourally Relevant Plant mentioning
confidence: 99%
“…A widely used definition of interaction types arises from frog ORN recordings Odour interactions in the moth MGC (Duchamp-Viret et al, 2003;Rospars et al, 2008): hypoaddivity is described as a response to the mixture, which is equal to or a little lower than the response to the strongest component; a response to the mixture lower than the strongest component is defined as suppression, and synergism is defined as a response to the mixture that is stronger than the response to the strongest component (Duchamp-Viret et al, 2003). All three interaction types have been found in insects at different neuronal levels from the analysis of responses to mixtures of general odorants and mixtures of pheromone components [honeybee (Deisig et al, 2006); moths (Martin and Hildebrand, 2010;Kuebler et al, 2011;Hillier and Vickers, 2011); Drosophila (Silbering and Galizia, 2007)].…”
Section: Introductionmentioning
confidence: 99%
“…We differentiated between two main network interaction types, synergism and suppression (Duchamp-Viret et al, 2003;Silbering and Galizia, 2007;Kuebler et al, 2011b). Our criteria were highly restrictive: to be considered as a suppressive interaction, at least one of the activity regions in the mixture pattern (black bars) had to completely disappear compared with the projected mixture (white bars).…”
Section: Input/output Comparison Reveals Al Network Modulation Emergementioning
confidence: 99%